From New Labour to Rudd/Gillard – transferring social policy. (2nd September 2016) - Manwaring, Rob
ABSTRACT: From 2007 to 2010, there were national Labour governments in Britain and Australia, the longest and only third time this had occurred since the second World War. The period of New Labour was closing in the UK, and in Australia the Rudd government came to power after 11 years in opposition, directly influenced by the, at times, trailblazing UK Labour government. In the domain of social policy, New Labour was a source of policy inspiration and transfer. Specifically, the Rudd/Gillard governments borrowed heavily its 'social exclusion' agenda, and also the use of 'compacts' with the third sector. This article examines the policy diffusion and transfer between the UK and Australia, and in doing so offers critical insights into the policy transfer literature. The article examines the reasons for the Australian Labor Party's adoption of these policies, and links this to wider dilemmas and identity crisis that are afflicting centre-left governments across the globe.